PEMANFAATAN APLIKASI LET’S READ ASIA DALAM PELESTARIAN BAHASA DAERAH DAN PENINGKATAN MINAT BACA ANAK - Latifa Choirunisa Santoso; Meilia Nurhayati; Mega Alif Marintan (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society, 2025)
Technology has had both positive and negative impacts. One of these impacts is in the field of literacy, which includes the use of local languages and interest in reading. The impact is the erosion of the use of local languages and the decline in interest in reading among children. However, on the other hand, technology can be utilized to solve these problems. One form of utilization is through the educational application Let's Read Asia. This digital application, initiated by Books for Asia from The Asia Foundation in 2019, presents hundreds of children's reading collections in various languages. The purpose of this research is to explore further the Let's Read Asia application in supporting the preservation of regional languages and increasing interest in reading so that later it can be redeveloped and recognized by the wider community as an educational application. The research method used is qualitative by conducting content analysis. This writing identifies various features of the Let's Read Asia application that contribute to efforts to preserve regional languages and increase children's literacy. The results show that Let's Read Asia is an application that provides thousands of digital reading books for children. This application not only acts as a means to preserve local languages but also encourages an increase in children's interest in reading through creatively designed and interactive features. Through the Let's Read Asia application, people can discover various regional languages and access reading materials practically.